A protease activation mutant, MVCES1, as a safe and potent live vaccine derived from currently prevailing Sendai virus. - Wang, X L (1994)
Sendai virus fresh isolates were shown to be antigenically different from the prototype Fushimi strain that had long been passaged in embryonated chicken eggs. Phylogenetic analysis of the hemagglutinin-neuraminidase genes also revealed the difference between these two virus groups. Both trypsin-resistant and elastase-sensitive mutations were additionally introduced to an LLC-MK2-cell-adapted and attenuated mutant derived from one of the fresh isolates. This protease activation mutant (MVCES1) showed the same antigenicity as the fresh isolates, and as a result of a single cycle of growth in lungs, it could confer better protection on mice against challenge infection with the currently prevailing Sendai virus than TR-5, which is a trypsin-resistant mutant derived from the Fushimi strain. The eligibility of MVCES1 as an attenuated live vaccine of Sendai virus is discussed.